FAKTOR MEMPENGARUHI KUNJUNGAN IBU MEMBAWA BALITA KE POSYANDU KELURAHAN TANJUNG PAUH TAHUN 2018 - Endra Amalia; Syahrida Syahrida; Yessi Andriani (JURNAL KESEHATAN PERINTIS, 2019)
Posyandu is one form of community-based health effort managed jointly the health development as an effort to get basic health services for the.Lack of support from family, the cadres and capital work affect a visit to posyandu.The purpose of this research is to find the, family support the cadres and capital work for the child mother brought to the posyandu.This study was conducted in january 2019, with the design cross sectional, and population of the research is all the mothers with children under five were 76. peopleThe sample in a simple. random samplingThe analysis univariat shows that most visit the child to the posyandu good category ( 65.8 % ), more than child separoh mother supported the poor ( 52.6 % ), the role of kaders kategiri less active ( 53.9 % ) and more than separoh mother working visit to the posyandu ( 56.6 % ).